Pattern Recognition by Melanoma Differentiation-Associated Gene 5 (Mda5) in Teleost Fish: A Review - Lazarte, Jassy Mary S.; Thompson, Kim D.; Jung, Tae Sung (Frontiers in Immunology, 2019)
Teleost fish, as with other vertebrates, rely on their innate immune system as a first line of defense against invading pathogens. A very important characteristic of the innate immune response is its ability to recognize conserved molecular structures, such as viral dsRNA and ssRNA. Mda5 is one of the three pattern recognition receptors (PRRs) that recognize cytoplasmic viral ligands. Teleost Mda5 is widely conserved among several fish species and possesses the same structural domains as those seen in their mammalian counterparts. Fish Mda5 has been shown to be capable of initiating an inflammatory response both in vitro (in different fish cell lines) and in vivo using synthetic viral analogues or virus. The interferon (IFN) pathway is triggered as a result of Mda5 activation, leading to the expression of type I IFNs, IFN- stimulated genes and pro-inflammatory cytokines. Although it is known that Mda5 acts as a receptor for virally-produced ligands, it has been shown more recently that it can also initiate an immune response against bacterial challenges. This review discusses recent advances in the characterization of teleost Mda5 and its potential role in antiviral and antibacterial immunity in teleost fish.